2007
DOI: 10.1182/blood-2007-02-073486
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene expression profiles of acute myeloid/T-lymphoid leukemia with silenced CEBPA and mutations in NOTCH1

Abstract: Gene expression profiling of acute myeloid leukemia (AML) allows the discovery of previously unrecognized molecular entities. Here, we identified a specific subgroup of AML, defined by an expression profile resembling that of AMLs with mutations in the myeloid transcription factor CCAAT/enhancer-binding protein alpha (C/EBP␣), while lacking such mutations. We found that in these leukemias, the CEBPA gene was silenced, which was associated with frequent promoter hypermethylation. The leukemias phenotypically sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
184
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(195 citation statements)
references
References 55 publications
7
184
2
2
Order By: Relevance
“…This suggests that TRIB2 degrades C/EBPα p42 via ubiquitination of K313 and duplication of this residue as occurs in AML patients samples would lead to an increase in C/EBPα p42 degradation in the presence of TRIB2. Patients with K313dup had TCR rearrangements and CD7 expression (27), lymphoid features associated with unfavourable outcome and which we have previously linked with TRIB2 and C/EBPα perturbation (31). Previous investigation of the combination of a C-terminal mutation (K313 duplication) with C/EBPα p30 expression revealed co-operation and provides a possible explanation for the high prevalence of one N-term mutation and one C-term mutation in ~90% of biallelic C/EBPα mutant AMLs (23).…”
Section: Discussionmentioning
confidence: 67%
“…This suggests that TRIB2 degrades C/EBPα p42 via ubiquitination of K313 and duplication of this residue as occurs in AML patients samples would lead to an increase in C/EBPα p42 degradation in the presence of TRIB2. Patients with K313dup had TCR rearrangements and CD7 expression (27), lymphoid features associated with unfavourable outcome and which we have previously linked with TRIB2 and C/EBPα perturbation (31). Previous investigation of the combination of a C-terminal mutation (K313 duplication) with C/EBPα p30 expression revealed co-operation and provides a possible explanation for the high prevalence of one N-term mutation and one C-term mutation in ~90% of biallelic C/EBPα mutant AMLs (23).…”
Section: Discussionmentioning
confidence: 67%
“…[146][147][148][149] Three mechanisms of CEBPA inactivation have been reported: (1) downregulation of CEBPA expression consecutive to the AML1-ETO fusion transcript in t(8,21) leukemia cells, interestingly conditional expression of CEBPA in these cells is sufficient to trigger granulocytic differentiation; 150 recently, Wouters et al reported that the CEBPA gene could also be silenced by promoter hypermethylation in a specific subtype of AML that phenotypically showed aberrant expression of T-cell genes such as CD7 or enhanced expression of TRIB2, suggesting aberrantly activated NOTCH signaling. 151 (2) Suppression of CEBPA function through inhibition of the translation of CEBPA mRNA by interaction with hnRNPE2, which is induced by BCR-ABL; 152 this mechanism could explain transition of chronic phase to myeloid blast crisis in CML by blocking myeloid differentiation and (3) other genetic abnormalities affecting CEBPA gene, particularly mutations, which have been reported in hematological malignancies, mainly in AML. 153 Acquired point mutations of the CEBPA gene have been reported in 89 of 965 (9%) AML patients in 7 studies including 12 M0-AML, 159 M1-AML, 203 M2-AML, 44 M3-AML, 101 M4-AML, 98 M5-AML, 8 M6-AML, 4 M7-AML and 15 secondary AML and 321 AML for which FAB or WHO classification was not mentioned.…”
Section: Cebpamentioning
confidence: 99%
“…We have previously shown that SFKs can negatively regulate myeloid differentiation. 8 In this report, we sought to determine whether treatment of AML cell lines and primary cells with dasatinib might restore or enhance ATRA-induced differentiation.…”
Section: Conflict Of Interestmentioning
confidence: 99%